Food systems transformation, animal-source foods consumption, inequality, and nutrition in Myanmar - Scott, Jessica M.; Belton, Ben; Mahrt, Kristi; Thilsted, Shakuntala H.; Bogard, Jessica R. (Springer, 2023)
This study traces the consumption of animal-source foods (ASF) during a period of rapid economic change and food system transformation in Myanmar. We use data from two nationally representative consumption surveys conducted in 2010 and 2015 and food composition tables to estimate the contributions of ASF to estimated average requirements (EARs) of key nutrients among population subgroups differentiated by geography and economic status. We find: (1) Little change in the average quantity of ASF consumed per individual, but substantial changes in the composition of the ASF consumed. (2) Increasing rural–urban and income-linked inequality in quantities of ASF and associated nutrients consumed. (3) Declines in the adequacy of intakes of five out of eight micronutrients (calcium, iron, zinc, thiamine, vitamin B12) and small increases in two (selenium and vitamin A), due to the changing composition of ASF; most importantly, reductions in the supply of diverse aquatic foods from capture fisheries and increasing availability of intensively reared chicken. (4) Elevated levels of ASF-derived total fat and sodium consumption among better-off consumers, suggesting an emerging triple burden of malnutrition. We review the implications of these results for food security, nutrition-sensitive policies and interventions beyond Myanmar.